Mechanics of collagen fibrils: A two-scale discrete damage model. (May 2016) - Linka, Kevin; Itskov, Mikhail
Abstract: Collagen is one of the most important structural proteins of biological tissues. Recently, a new damage phenomena caused by a mechanical overloading of the tendon has been revealed on the collagen fibril level by means of scanning electron microscopy (Veres et al., 2013 ). In order to describe this phenomena we propose in the present paper a constitutive damage model for single collagen fibrils. It utilizes a statistical framework in order to incorporate a physically motivated transition from the entropic- to the intrinsic-elasticity range of single tropocollagen molecules. In this two-scale approach a bridging relation between the tropocollagen and fibril level as well as a failure criterion after exceeding a critical stretch limit are introduced. The final constitutive relations are validated against experimental data available in literature for both, the reversible and the irreversible, stress–strain response.